Large-N kinetic theory for highly occupied systems - Walz, Roland; Boguslavski, Kirill; Berges, Jürgen (Arxiv, 2017)
We consider an effective kinetic description for quantum many-body systems, which is not based on a weak-coupling or diluteness expansion. Instead, it employs an expansion in the number of field components N of the underlying scalar quantum field theory. We demonstrate that the large-N kinetic theory at next-to-leading order is able to describe important aspects of highly occupied systems, which are beyond standard perturbative kinetic approaches. We analyze the underlying quasiparticle dynamics and solve the large-N kinetic equation for a highly occupied system far from equilibrium. This allows us to compute universal self-similar properties at nonthermal fixed points, including the infrared scaling form of the distribution function.
Identifizierung der Ressource nach: Last revised 27 Aug 2018
Gesehen am 08.12.2020